Tourism, land, and landscape in Ireland - James, Kevin J., author.
1 online resource (xiv, 208 pages)
Keywords: "This study, exploring a broad range of evocative Irish travel writing from 1850 to 1914, much of it highly entertaining and heavily laced with irony and humour, draws out interplays between tourism, travel literature and commodifications of culture. It focuses on the importance of informal tourist economies, illicit dimensions of tourism, national landscapes, 'legend' and invented tradition in modern tourism" --